Desenvolvimento de matriz extracelular descelularizada (Scaffold) de pele de tilápia como novo biomaterial para aplicação em medicina regenerativa - Mendoza Hernández, Eleicy Nathaly (2020)
Scaffolds are biomaterials composed of decellularized extracellular matrix (MEC), widely used in developed countries. During the production of scaffolds, MEC is isolated from its native cells and genetic material to produce a biomaterial with structural, biochemical and biomechanical characteristics of the original tissue. Collagen is a major component of scaffolds. In this context, Nile Tilapia skin appears as a new biomaterial useful for bioengineering, due to its mechanical properties and similarity in histological composition. The objective of this work was to develop a decellularized extracellular matrix from the tilapia skin as a new biomaterial for application in regenerative medicine. In this work, different physical, chemical and enzymatic methods were studied for the decellularization of tilapia skin, in order to obtain a scaffold with the best possible quality. Twelve (12) decellularization protocols were developed and tested, using ionic and non-ionic surfactants, such as sodium Dodecyl sulfate, sodium deoxycholate, Triton X-100, Tween 20, CHAPS and Nonidet P-40, with the purpose of eliminate cells (evaluated by DAPI staining), maintain the structure (evaluated by HE) and do not cause cytotoxicity. The best protocols tried were Tween 20 for 24h, CHAPS 8 mM for 4h and Triton X-100 at 1% for 6h, with decellularization percentages of 100%, 96.35% ± 3.65% and 97.83% ± 2.17% and were approved in the indirect cytotoxicity test for having cell viability of 86.71% ± 2.24%, 108.3% ± 6.49% and 95.63% ± 3.62%; respectively. The ideal irradiation dose for radio-sterilization was determined using the scaffolds produced by the CHAPS 8 mM protocol and testing with doses of 15 25, 30 and 50 kGy. With these results we conclude that the scaffolds produced from Tween 20 for 24h, CHAPS 8 mM for 4h and Triton X-100 at 1% for 6h have potential for application as biomedical materials, as they are the best in decellularization, maintaining the structure of fibers and not causing cytotoxicity. Additionally, the 25 kGy dose was considered the best for irradiation.